Persijilan MS ISO 9002 dan persepsi kakitangan terhadap amalan pengurusan kualiti : satu kajian kes di Bintulu Port Sdn. Bhd. - Adibah, Binti Ismail. (1999)
The purpose of this study was to identify the level of quality management practices after the company receiving MS ISO certification. In addition this study aimed to investigate the type of management involvement and commitment in quality activities, employees knowledge about the company quality policy and how company evaluate customers' satisfaction. Six dimensions on quality practices being considered in this study were : leadership, strategic quality planning, information and analysis, human resource management and development, quality management processes, and focus and customers' satisfaction. The respondents for this study were ninety three workers who represented four departments of Bintulu Port Sdn. Bhd.